HUBUNGAN ANTARA WORK-FAMILY CONFLICT DENGAN KEPUASAN PERNIKAHAN PADA PEREMPUAN YANG TERMASUK DALAM GENERASI SANDWICH - Jessica Jetta Pangaribuan; Ratriana Yuliastuti Endang Kusumiati (Bajang Institute, 2026)
This study aims to examine the relationship between Work-Family Conflict (WFC) and marital satisfaction among sandwich generation women. The participants consisted of 251 women aged 30–50 years in Indonesia, with data collected through an online questionnaire. The instruments used were the Work-Family Conflict Scale (WFCS) developed by Carlson, Kacmar, and Williams (2000), which includes three aspects: time-based conflict, strain-based conflict, and behavior-based conflict, and the ENRICH Marital Satisfaction Scale (EMS) developed by Olson and Fowers (1993), which includes ten aspects of marital satisfaction. Data analysis involved descriptive statistics, normality and linearity tests, and Spearman’s rho correlation. The results indicated no significant relationship between work-family conflict and marital satisfaction (r = 0.007, p = 0.457). The average score of work-family conflict was 64.90 (SD = 14.176) and was classified in the moderate category, while the average score of marital satisfaction was 37.33 (SD = 12.239), which was also in the moderate category, indicating that the respondents had work-family conflict and marital satisfaction levels in the moderate category.